Do Female Directors Enhance ESG Performance? The Moderating Role of FinTech in Indonesian Banking - Meiliana Suparman; Riska Hariyanti; Sheila Septiany (Research of Accounting and Governance, 2026)
This study examines the effect of female representation on the board of directors on environmental, social, and governance (ESG) performance in the banking sector. The rapid growth of financial technology (FinTech) creates a governance phenomenon by potentially reshaping how board diversity influences sustainability outcomes. This study uses panel data from Indonesian listed banks and analyzes 230 firm-year observations from 2019 to 2023. This study applies moderated regression analysis (MRA) to test the proposed relationships. The findings show that female representation on the board of directors improves ESG performance. However, FinTech development weakens the positive effect of female directors on ESG performance, indicating that higher levels of digitalization reduce the effectiveness of board gender diversity in promoting sustainability. This study concludes that digital transformation alters the role of board governance mechanisms in achieving ESG objectives. This study provides managerial and regulatory implications by emphasizing the importance of aligning FinTech strategies with board governance practices to ensure that digitalization supports, rather than undermines, corporate ESG commitments and long-term sustainability.